Changes in hematoma volume following aneurysmal subarachnoid hemorrhage and its impact on patient prognosis - Huang, Zhenshan; Qian, Feng; Ma, Kui; Jiang, Guowei; Zhang, Lianfu; Zhang, Yongming (Frontiers in Neurology, 2025)
ObjectiveThis study aims to investigate the effects of preoperative intracerebral hematoma volume (HVpre), hematoma volume 6–8 days post-surgery (HVpost), and the rate of hematoma volume change (HVpre−HVpost)/HVpre on the prognosis of patients with aneurysmal subarachnoid hemorrhage (aSAH).Materials and methodsCT imaging data from 62 aSAH patients admitted to our hospital’s Neurosurgery Department between January 2022 and December 2023 were obtained, both preoperatively and 6–8 days postoperatively. The hematoma volumes were measured using 3D-Slicer. Patients’ recovery at 3 months post-discharge was assessed using the Modified Rankin Scale (mRS), categorizing the patients into a good prognosis group (mRS score 1–2) and a poor prognosis group (mRS score 3–5). Multivariate logistic regression analysis was conducted to identify independent risk factors for poor prognosis. Statistical methods were employed to compare preoperative and postoperative hematoma volumes with commonly used clinical scores. The predictive value of HVpre and HVpost for poor prognosis was evaluated using ROC curves. The rate of volume change was stratified by interquartile ranges, and the impact of different change rates on prognosis was compared.ResultsSignificant differences were found between good and poor prognosis groups in age, GCS score, Hunt-Hess grade, mFisher grade, BVpre, BVpost, and (HVpre−HVpost)/HVpre (p < 0.05). Logistic regression identified gender, age, BVpre, BVpost, and volume change rate as independent risk factors (p < 0.01). Increased GCS scores and higher Hunt-Hess and mFisher grades correlated with increased HVpre and HVpost. Higher hemorrhage reduction rates were linked to better outcomes. ROC curves showed HVpre and HVpost AUC values (0.831 and 0.857, respectively) were significantly higher than clinical scales. An HVpre volume over 22.25 mL and HVpost over 15.67 mL indicated a higher risk of poor prognosis, with sensitivities of 79.3 and 80.7%, and specificities of 67.1 and 69.3%.ConclusionHVpre, HVpost, and (HVpre−HVpost)/HVpre can serve as neuroimaging biomarkers for assessing patients after aSAH and can effectively predict clinical prognosis.